2019
DOI: 10.1089/scd.2019.0075
|View full text |Cite
|
Sign up to set email alerts
|

The Atrioventricular Junction: A Potential Niche Region for Progenitor Cells in the Adult Human Heart

Abstract: A stem cell niche is a microenvironment where stem cells reside in a quiescent state, until activated. In a previous rat model, we combined 5-bromo-2-deoxy-uridine labeling with activation of endogenous stem cells by physical exercise and revealed a distinct region, in the atrioventricular junction (AVj), with features of a stem cell niche. In this study, we aim to investigate whether a similar niche exists in the human heart. Paired biopsies from AVj and left ventricle (LV) were collected both from explanted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…The study was approved by the local ethics committee at the University of Gothenburg (#436–15, #596–11) and carried out in accordance with the Helsinki Declaration as revised 2013. Biopsy material from some of the patients were also used in other previously published studies or unpublished studies due to the limited supply of biopsy material [ 24 26 ]. No organs/tissues were procured from prisoners.…”
Section: Methodsmentioning
confidence: 99%
“…The study was approved by the local ethics committee at the University of Gothenburg (#436–15, #596–11) and carried out in accordance with the Helsinki Declaration as revised 2013. Biopsy material from some of the patients were also used in other previously published studies or unpublished studies due to the limited supply of biopsy material [ 24 26 ]. No organs/tissues were procured from prisoners.…”
Section: Methodsmentioning
confidence: 99%
“…Subepicardial regions have been indicated as preferential locations for CSC niches in the adult heart (Di Meglio et al, 2010;Limana et al, 2010). However, they can also be found scattered throughout the myocardium, particularly in the atria and apex, cardiac regions characterized by low hemodynamic stress (Vukusic et al, 2019). Experiments on CSC localization have been mostly carried out in rodents (Barreto et al, 2019).…”
Section: Heartmentioning
confidence: 99%
“…In addition, SCA1‐expressing CSCs were only demonstrated in mice, whereas no human homolog has yet been identified (Holmes & Stanford, 2007 ). According to Vukusic et al (Vukusic et al, 2019 ), the atrio‐ventricular junction at the insertion point of the mitral valve may represent a crucial niche region, from which CSCs would promote regeneration processes for both the valve, atria, and ventricles.…”
Section: Heartmentioning
confidence: 99%
“…In addition, we found expression of the stem cell markers MDR1 and Sca1. In a follow-up study on the human left AVj, the base of the mitral valve, we observed expression of biomarkers associated with hypoxia, stem cells, proliferation, and migration, showing features of a progenitor niche [ 18 ].…”
Section: Introductionmentioning
confidence: 99%